Dari Gen Z Menuju Pemuda Islam Berdaya Saing: Peran PAI dalam Pembentukkan Life Porpose (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2026)
Generation Z faces various challenges in determining their life direction amidst increasingly complex technological developments and social dynamics. As part of this generation, 12th-grade Vocational High School (SMK) students are in a crucial transition phase towards the world of work and further education, thus requiring the strengthening of a clear life purpose based on Islamic values. This community service activity aims to strengthen the role of Islamic Religious Education (PAI) in shaping the life purpose of vocational high school students as an effort to create competitive Muslim youth. The community service activity was carried out at SMK Abdi Negara Tangerang, targeting 12th-grade students using an educational, participatory, and reflective approach. The implementation methods included interactive lectures, discussions, self-reflection, and mentoring linked to the values ​​of Islamic Religious Education. Data collection techniques were carried out through observation, short interviews, and documentation, while data analysis used a qualitative descriptive approach. The results of the activity showed an increase in students' understanding of the importance of having a directed life purpose that is aligned with the values ​​of faith, morals, and social responsibility. In addition, students showed increased motivation, awareness of their potential, and readiness to face the future. This activity also strengthens the role of Islamic Religious Education as a means of character development and life orientation for students. Thus, this community service activity makes a positive contribution to shaping a young generation of Muslims with character, competitiveness, and a clear purpose in life.